Antifungal Activity of Trichoderma orientale FMR 12486 Crude Extract against Some Human Pathogenic Fungi - Assi, Sura Rasan; Al-Aaraji, Alaa Mohsin (Iraqi Journal of Science, 2024)
This work aimed to investigate the prevalence of pathogenic fungi and evaluate the antifungal activity of Trichoderma orientale FMR12486 crude extract against pathogenic fungi isolated from patients attending the National Center for Thoracic and Respiratory Diseases (having a history of tuberculosis) and consultant of Dermatology of Baghdad hospital, Iraq. A total of 80 clinical specimens were collected: 20 skin scrapings specimens and 60 sputum specimens. The results of direct examination by KOH 10% and culture showed that 11 (55%) cases from 20 skin specimens were positive for fungal infections, while in the sputum specimens, 28 (47%) cases from 60 were positive. Candida albicans represented the most common fungal infection isolated from sputum specimens which represented 18 cases at a rate of 64.2%, followed by Candida tropicalis 5 (17.9%), Aspergillus fumigates 2 (7.1%), Aspergillus flavus 1 (3.6%), Candida glabrata 1 (3.6%) and Candida krusei 1 (3.6%). While in the skin scrapes, Candida parapsilosis was the common which represented 3 cases at a rate of 27.3%, followed by Trichophyton mentagrophyte 2 (18.2%), Microsporium canis 2 (18.2%), C. albicans 2 (18.2%), Trichophyton rubrum 1 (9.1%), C. tropicalis 1 (9.1%). T. orientale isolates were collected from the gardens soil of the University of Baghdad and were then identified depending on the morphological feature of the colony and microscopic characteristics. To confirm identification, PCR technique was used in which DNA of T. orientale was extracted at a concentration of 54 - 294 μg/2 g wet mycelium with a purity of 1.6 - 1.8. DNA samples were amplified with primers ITS-1and ITS-4, And the results confirmed that the isolate was T. orientale strain FMR12486. This isolate was processed with ethyl acetate using a standard extraction method and the final amount of crude extract being 6 grams. Different concentrations of crude extract 0.5, 1, 2 and 4 mg/ml were prepared and used against fungal pathogens isolated using the agar-well diffusion method. The results showed high antifungal activity against pathogenic isolates, significantly recording maximum inhibition zones of 20 and 22 mm against C. parapsilosis at concentrations of 0.5 and 1 mg/ml, respectively. It was followed by T. mentagrophyte and C. glabrata. 16, 20, and 16, 20 mm that were recorded at concentrations of 2 and 4mg/ml, a significant maximum inhibition zone was recorded 26 mm against C. glabrata, followed by C. parapsilosis, M. canis and T. mentagrophyte (24, 26; 16, 24 and 20, 24mm respectively). Just Trichophyton rubrum fungus in this study showed resistance to all concentrations of the crude extract where the inhibition zone was zero. The results of the current study showed that T. orientale strain FMR12486 crude extract can be used to make an effective drug to treat human fungal infections.